Iodine-Supported Hip Implants: Short Term Clinical Results. (28th October 2015) - Kabata, Tamon; Maeda, Toru; Kajino, Yoshitomo; Hasegawa, Kazuhiro; Inoue, Daisuke; Yamamoto, Takashi; Takagi, Tomoharu; Ohmori, Takaaki; Tsuchiya, Hiroyuki
Abstract : We developed a new povidone iodine coating technology for titanium hip implants and performed a clinical trial to assess its usefulness in suppressing postoperative infection. Results indicate that iodine-supported titanium has favorable antibacterial activity, biocompatibility, and no cytotoxicity. Thirty joints in 28 patients were treated using iodine-supported implants. Fourteen joints were revision total hip arthroplasty (THA) after periprosthetic infection, 13 were primary THA for immunosuppressive conditions or pyogenic arthritis, and 3 were conversions from hemiarthroplasty to THA for immunosuppressive conditions. Two examinations were conducted sequentially until final follow-up: white blood cell (WBC) and C-reactive protein (CRP) were measured pre- and postoperatively and thyroid hormone levels in the blood were examined. The mean follow-up period was 33 months (14–78). There were no signs of infection in any patient at the last follow-up. WBC and CRP levels returned to normal within several weeks. No abnormalities of thyroid gland function were detected. Loosening of the implants did not occur in any patient. Excellent bone ingrowth and ongrowth were found around prostheses. No cytotoxicity or adverse effects were detected. These results suggest that iodine-supported THA implants can be highly effective in preventing and treating postoperative infections.